Sakral dan Profan (Sistem Kepercayaan Suku Akit di Bantan Tengah) - Sahrul Sori Alom Harahap (Akademika: Jurnal Keagamaan dan Pendidikan, 2021)
Akit with a belief system that is unique enough to become an interesting discourse, the belief system is "wrapped up" like the belief in general, where Akit tribal leaders are customarily ordained and chosen by ancestors intended as intermediaries to bridge the ancestral spirits with their descendants to get the blessing of a good life sustainable, then the realm that is considered sacred must be offered with various offerings. The offering itself has a certain time and certain components to be offered to the ancestors and only the chosen ones can offer it directly. The profane realm is considered a supporting medium that does not have to be held and is considered not to violate sacred offerings.